PENGARUH LIKUIDITAS, PROFITABILITAS DAN PERTUMBUHAN PENJUALAN TERHADAP MODAL KERJA PADA PERUSAHAAN PT. UNILEVER INDONESIA Tbk. - Sri Intan Purnama (Sekolah Tinggi Ilmu Ekonomi La Tansa Mashiro, 2019)
The research objective was to study the effect of liquidity, profitability and sales growth of the working capital at PT. Unilever Indonesia Tbk.The study was conducted on the financial statements issued every quarter from the first quarter of 2009 until the second quarter of 2016. Thirty financial statements have been used as the sample was selected using a sampling technique that is boring sampling nonprobabilitas. The data have been processed by the regression procedure. The results showed the following: (1) Found effect of liquidity to working capital, (2) did not find the effect of profitability to working capital, (3) did not find the effect of growth in sales to working capital, (4) found the effect of liquidity, profitability and sales growth jointly to working capital.Finally, the conclusion of this research is that partially proved that there are significant liquidity to working capital but profitability and sales growth there is no effect on working capital. While simultaneously liquidity, profitability and sales growth there is an influence on the working capital. It further showed that the liquidity, profitability and sales growth can simultaneously be a consideration in strategic planning to improve working capital management in the institution studied.